Analisis Strategi Pemasaran Pada PT. Central International Education - Tri Veny Pitri; Muji Gunarto (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
The aim of this study was to decide the marketing strategy of PT. Central International Education by using SWOT analysis ,so it could be conclude that there were some internal factors that had stength such as cleanliness, a large parking area, good and reliable services, and products with good quality. meanwhile, there were some weaknesses such complains handling which was still not maximum, less promotion strategies and employees coming late to the office. some external factors were marketing opportunities, target market, product quality and good relationship with customers. there were also some threats such as business competitor s, government rule and new competitors. some strategies that can be used in future are giving good and quick responses to customers, improving promotion strategies, improving company services to ensure the cumtomers, maximizing promotion and advertisments to attract the customers and extending the market regions.